Up and downregulation of p16 Ink4a expression in BRAF-mutated polyps/adenomas indicates a senescence barrier in the serrated route to colon cancer - Kriegl, Lydia; Neumann, Jens; Vieth, Michael; Greten, Florian R.; Reu, Simone; Jung, Andreas; Kirchner, Thomas (Modern Pathology, 2011)
P16Ink4a is an important factor in carcinogenesis and its expression can be linked to oncogene-induced senescence. Oncogene-induced senescence is characterized by growth arrest and occurs as a consequence of oncogene activation due to KRAS or BRAF mutation. It has been shown that the induction of p16Ink4a in premalignant lesions and its loss during malignant transformation is an important mechanism in the carcinogenesis of several tumours. Loss of p16Ink4a is often caused by CDKN2A promoter hypermethylation. This mechanism of gene silencing is associated with the CpG island methylator phenotype (CIMP) in colorectal carcinomas, which is characterized by widespread promoter methylation. In particular, colorectal carcinomas with BRAF mutations have been shown to be strongly associated with CIMP. Also, BRAF mutations are strongly correlated with the serrated route to colorectal cancer. In this study, we investigated p16 Ink4a expression and promoter methylation in BRAF-mutated serrated lesions of the colon. P16 Ink4a expression was found to be upregulated in premalignant lesions and was lost in invasive serrated carcinomas. P16Ink4a expression and Ki67 expression were mutually exclusive, indicating that p16Ink4a acts as cell cycle inhibitor. Additionally, progression of malignant transformation in serrated lesions was accompanied by increasing methylation of the CDKN2A promoter. Therefore, our data provide evidence for oncogene-induced senescence in the serrated route to colorectal cancer with BRAF mutation and upregulation of p16Ink4a expression appears to be a useful indicator of induction of senescence. Loss of p16Ink4a expression occurs during malignant transformation and is caused mainly by aberrant methylation of the CDKN2A promoter. © 2011 USCAP, Inc. All rights reserved.
CRIS-Team Scopus Importer:2025-03-05
Keywords: BRAF mutation; hypermethylation; Ki67; p16; serrated route